Acyl‐Imidazoles: A Privileged Ester Surrogate for Enantioselective Synthesis. Issue 23 (4th June 2019) - Lauberteaux, Jimmy; Pichon, Delphine; Baslé, Olivier; Mauduit, Marc; Marcia de Figueiredo, Renata; Campagne, Jean‐Marc
Abstract: Since the first report by Evans in asymmetric Friedel‐Crafts reactions, the use of acyl‐imidazoles has blossomed as powerful ester/amide surrogates. The imidazole scaffold indeed displays stability and special activation features allowing both better reactivity and selectivity in traditional ester/amide functionalizations: α‐(enolate chemistry), β‐(conjugate additions), α, β‐(cycloadditions) or γ/δ‐(vinylogous). An overview of the contemporary and growing interest in acyl‐imidazoles in metal‐ and organo‐catalyzed transformations (bio‐hybrid catalytic systems will be fully described in a back‐to‐back Minireview) will be highlighted. Moreover, post‐functionalization expediencies are also going to be discussed in this Minireview. Abstract : What a privilege ! Since their first use in asymmetric Friedel‐Crafts reactions, acyl‐imidazoles have appeared as powerful ester/amide surrogates. Indeed, the imidazole moiety displays stability and special activation features that allow enhanced reactivity and selectivity in traditional ester/amide functionalization. An overview of the contemporary and growing interest for acyl‐imidazoles in metal‐ and organo‐catalyzed transformations, as well as post‐functionalization expediencies will be highlighted.